Associated Systemic Risk Factors and Neuro-imaging Findings of Unilateral Optic Disc Swelling in a Bangladeshi Population (American Journal of Medical Science and Innovation, 2025)
The presence of unilateral optic disc swelling (ODS) is linked to several illnesses, such as hypertension and diabetes mellitus. While the incidence of diabetes is increasing in Bangladesh, not much is known about its systemic links in the local population. This study aims to evaluate the relationships between systemic factors and unilateral optic disc swelling among people in Bangladesh. A cross-sectional observational study was done at the Neuro-Ophthalmology Department in Dhaka from March 2019 to July 2020, covering 105 patients with unilateral ODS. Eye health was evaluated clinically, visual functioning was measured, and brain scans were performed for diagnosis. Basic demographics, historical details, and results from blood tests (CBC, RBS, HbA1c, lipid profile, CRP) were all collected with the use of structured forms. The statistical analysis was done using SPSS version 26.0, and the level of significance was p